PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP NEGERI 17 PADANG - Evita, Yulia; Rahmi, Rahmi; Husna, Husna (Pendidikan Matematika, 2013)
This research is motivated by the students understanding of mathematical concepts are still low, students are afraid to ask the teacher, and most students do not have textbooks. This study aims to determine whether students understanding of mathematical concepts with cooperative learning models Handout Think Pair Share with a better understanding of mathematical concepts than students with conventional learning. This type of research is experimental research, the design of randomized trials on the subject. The study population was a student of class VII Padang SMP 17 Academic Year 2012/2013 consisting of nine classes. Technique of random sampling, the sample is selected as the class as a class VII3 VII6 as experimental and control classes. The research instrument was a test of understanding of mathematical concepts. Form of test used is a form of essay with a reliability test is r_11 = 0.87. The data analysis technique used is the one party t test with MINITAB. Based on the analysis of the data found that the two classes are normally distributed and homogeneous samples at significance level Î± = 0.05. Hypothesis test results obtained P-value = 0.000 is less than Î± = 0.05, then the hypothesis in this study received. It can be concluded that the students understanding of mathematical concepts cooperative learning models Handout Think Pair Share with a better understanding of mathematical concepts than students with conventional learning.